Modulation of lung cancer cell plasticity and heterogeneity with the restoration of cisplatin sensitivity by neurotensin antibody. (1st March 2019) - Wu, Zherui; Fournel, Ludovic; Stadler, Nicolas; Liu, Jin; Boullier, Agnès; Hoyeau, Nadia; Fléjou, Jean François; Duchatelle, Véronique; Djebrani-Oussedik, Nouzha; Agopiantz, Mikaël; Ségal-Bendirdjian, Evelyne; Gompel, Anne; et al.
Abstract: Overall survival of patients with metastatic non-small cell lung cancer (NSCLC) has significantly improved with platinum-based salt treatments and recently with targeted therapies and immunotherapies. However, treatment failure occurs due to acquired or emerging tumor resistance. We developed a monoclonal antibody against the proform of neurotensin (LF-NTS mAb) that alters the homeostasis of tumors overexpressing NTSR1. Neurotensin is frequently overexpressed along with its high affinity receptor (NTSR1) in tumors from epithelial origins. This ligand/receptor complex contributes to the progression of many tumor types by activation of the cellular effects involved in tumor progression (proliferation, survival, migration, and invasion). We demonstrate that LF-NTS mAb operates on the plasticity of tumor cells overexpressing NTSR1 and lowers their aggressiveness. The mAb enables the restoration of platinum-based therapies responsiveness, while also decreasing metastatic processes. Efficacy dosage with long-term treatment showed no obvious adverse events, while demonstrating improvement in the performance status. Our data suggests that LF-NTS mAb is an ideal candidate to be safely added to the conventional standard of care in order to improve its efficacy. Highlights: Neurotensin targeted therapy decreases tumor growth and metastasis processes, while restoring drug responsiveness. Neurotensin targeted therapy creates no additional toxicity. Neurotensin targeted therapy improves performance status.